EMBODIED DHARMA: SOCIOLOGICAL PERSPECTIVES ON HINDU RITUAL AND EVERYDAY LIFE - I Nyoman Subrata (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
This article explores how dharma becomes embodied through the ritual practices and everyday life of Hindu communities. Using a sociological lens, the study examines how rituals, gestures, spatial arrangements, and habitual actions function as embodied expressions of moral order, cultural identity, and social cohesion. Drawing on theories of embodiment (Merleau-Ponty), symbolic interactionism (Goffman), and interpretive anthropology (Geertz), the analysis reveals that dharma is not merely a philosophical doctrine but a lived social reality enacted through mindful practices, communal participation, and embodied discipline. Through ethnographic insights from Hindu ritual spaces in Bali and India, this study demonstrates how daily offerings, temple routines, bodily movement, and ritual choreography reinforce collective memory, negotiate cultural meaning, and maintain social harmony. The article contributes to sociological discussions on religion by showing how sacred values become material, sensory, and performative in contemporary Hindu life.